2014
DOI: 10.1038/mt.2014.23
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial-Mediated Knockdown of Tumor Resistance to an Oncolytic Virus Enhances Therapy

Abstract: Oncolytic viruses (OVs) and bacteria share the property of tumor-selective replication following systemic administration. In the case of nonpathogenic bacteria, tumor selectivity relates to their ability to grow extracellularly within tumor stroma and is therefore ideally suited to restricting the production of bacterially produced therapeutic agents to tumors. We have previously shown the ability of the type 1 interferon antagonist B18R to enhance the replication and spread of vesicular stomatitis virus (VSV)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 36 publications
1
27
1
Order By: Relevance
“…In vitro, VSV-DM51 infection was greatly enhanced by the B18R produced from E. coli in HT29 cells. In vivo, E. coli-B18R increased VSV replication and tumour destruction in HT29 and LLC subcutaneous tumours in athymic mice [104].…”
Section: Combining Vsv With Radiotherapymentioning
confidence: 93%
“…In vitro, VSV-DM51 infection was greatly enhanced by the B18R produced from E. coli in HT29 cells. In vivo, E. coli-B18R increased VSV replication and tumour destruction in HT29 and LLC subcutaneous tumours in athymic mice [104].…”
Section: Combining Vsv With Radiotherapymentioning
confidence: 93%
“…For example, Le Boeuf et al demonstrated that VSV (Vesicular Stomatitis Virus) combined with VACV (Vacienia Virus) improved antitumor response in immunodeficient and immunocompetent mouse tumor models (32). Cronin et al showed that intravenous application of nonpathogenic E. coli expressing the vaccinia type 1 IFN antagonist B18R augmented subsequent therapy with oncolytic VSV by overcoming innate immunity against oncolytic viruses in an athymic nude mouse model (33).…”
Section: Combination Therapies With Oncolytic Virusesmentioning
confidence: 99%
“…Given their unique capacity for selective growth in tumor tissue, therapeutics may be locally produced within the tumor by administered engineered bacteria (28)(29)(30)(31)(32)(33)(34). Bacteria can also be engineered to "sense" their environment, using synthetic biology approaches, further increasing their therapeutic or diagnostic power (35)(36)(37).…”
Section: Bacteria As Therapeutic Agentsmentioning
confidence: 99%